God and Charles Dickens : recovering the Christian voice of a classic author - Colledge, Gary. (Grand Rapids, Mich. : Brazos Press, 2012)
Gary Colledge examines Dickens's novels, letters, and other writings to explore his Christian thought and worldview. Chapters examine Dickens's life and work topically, arguing that Christian faith was front and center in some of what he wrote (such as his children's work The Life of Our Lord) and saliently implicit throughout various other characters and plots. --from publisher description.
Charles Dickens : that great Christian writer -- Charles Dickens's Jesus -- Charles Dickens : theologian? -- Charles Dickens : resurrectionist -- Real Christianity -- Dickens and the Church -- Reading (and hearing) Dickens.
Includes bibliographical references (pages 191-196) and indexes.
Keywords: Dickens, Charles, -- 1812-1870 -- Criticism and interpretation; Christianity and literature; God in literature